2017
DOI: 10.1038/s41598-017-06319-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct binding to GABARAP family members is essential for HIV-1 Nef plasma membrane localization

Abstract: HIV-1 Nef is an important pathogenic factor for HIV/AIDS pathogenesis. Studies have shown that the association of Nef with the inner leaflet of the plasma membrane and with endocytic and perinuclear vesicles is essential for most activities of Nef. Using purified recombinant proteins in pull-down assays and by co-immunoprecipitation assays we demonstrate that Nef binds directly and specifically to all GABARAP family members, but not to LC3 family members. Based on nuclear magnetic resonance (NMR) experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…On the other hand, we observed more inter-microcluster H-bonds in HP2 of GABARAP proteins (21) than LC3 (19), indicating tighter packing in GABARAP proteins. Previous reports also suggested similar observations where two-dimensional (2D) 1H-15N-heteronuclear single quantum coherence (HSQC) spectra showed HP2 to be more affected than HP1 on HIV-1 Nef binding to GABARAP [45]. It has also been reported that KBTBD6 engages with the bulkier residues of HP2 in GABARAP proteins, thus, forming tight-complex contributing to high binding affinity [25].…”
Section: Non-covalent Interactions and Binding Mode Differ Across Hsasupporting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, we observed more inter-microcluster H-bonds in HP2 of GABARAP proteins (21) than LC3 (19), indicating tighter packing in GABARAP proteins. Previous reports also suggested similar observations where two-dimensional (2D) 1H-15N-heteronuclear single quantum coherence (HSQC) spectra showed HP2 to be more affected than HP1 on HIV-1 Nef binding to GABARAP [45]. It has also been reported that KBTBD6 engages with the bulkier residues of HP2 in GABARAP proteins, thus, forming tight-complex contributing to high binding affinity [25].…”
Section: Non-covalent Interactions and Binding Mode Differ Across Hsasupporting
confidence: 56%
“…In a high-throughput study, LC3/GABARAP subfamilies display interactome differences where around one-third of binding partners were found to be specific for LC3 subfamily, one-third for GABARAP and one-third were found to be common for both groups [18]. At the molecular level, many reports have identified unique binders to HsAtg8 orthologs [21,[23][24][25][26][27][28][29][30]45]. We, therefore, surmised that molecular differences between bound complexes of human Atg8 orthologs would entail underlying mechanisms into their selectivity.…”
Section: Recognition Binding Variabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…Beyond their well-established role in autophagy, Atg8 proteins may be implicated in aging processes in additional, previously unanticipated ways. Results from our laboratory suggest that mammalian GABARAP subfamily members are required for secretion processes generating extracellular vesicles ( Boeske et al, 2017 ). If produced by challenged cells, such vesicles may carry altered macromolecules serving as damage-associated molecular patterns (DAMPs), or signaling molecules such as microRNAs, possibly contributing to a chronic low-grade auto-inflammatory state characteristic of organismal aging ( Franceschi et al, 2017 ) as well as cell-to-cell propagation of a senescent phenotype ( Eitan et al, 2016 ).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Thus, most GABARAP interaction partners have been found to bind GABARAPL1 and -L2 as well. For example, all three GABARAPs interact with ALFY in aggrephagy, with TRIM5a in antiviral xenophagy and with HIV-1 Nef in viral budding [45,54,79]. Whether one of the three proteins is the major interaction partner remains, however, unclear.…”
Section: Gabarapl1: G-aminobutyric Acid Receptorassociated Protein-limentioning
confidence: 99%